Speech Disfluency Made by Indonesian EFL Learners in Various Settings - Ahmad Samingan; Rudi Hartono; Novi Rahmania Aquariza; Suhono; Anzar Aquil (Bulletin of Pedagogical Research, 2025)
This research aimed to find out the types of speech disfluencies, to find out the frequencies of each type of speech disfluency, to find out the most dominant type of speech disfluencies, and to find out the factors that contribute to speech disfluency made by Indonesian EFL learners in various settings. This is qualitative research. Techniques of collecting data used in this research are documentation, recording, and interview. The research findings show that there are 7 types of speech disfluency made by EFL students of UIN Salatiga in various settings, namely filler, silent pause, repetition, prolongation, false start, grammatical error, and correction. The frequencies of speech disfluency are fillers 339 (47,70%), silent pause 76 (10,70%), repetition 69 (9,70%), prolongation 37 (5,20%), false start 24 (3,30%), grammatical error 136 (19,10%), and correction 29 (4%). The most dominant type of speech disfluency is fillers, with a total of 339 times (47,70%). Two factors contribute to speech disfluency, namely the cognitive factor and the psychological factor.